(3ehGgH GddWja aj aVd GdebGe GdTQjas - (3TeS GdOjf eMeO Hf CMeO Hf TQa GdOjf GdeOfj GdTGaYj, GHf TQa GdOjf,J (B904 (3g` s
(3ChdgG (B:s
(3hHYO , abO GWdYJ Ydi eGai gPg GdeedcI GdTQjaI ef GdCef hGdCeGf aYdeJ Cf Pdc HhdGjI ehdGfG GdSdWGf Gdedc GdCTQa bGfUhg GdZhQi s
(3BNQgG (B:s
(3Gddge GZaQ deDdag abjQ QMeI QHg eMeO Hf CMeO Hf TQa GdOjf GdTGaYj NGOe GdTQY GdTQja HGdeOjfI GdTQjaI hGdYde Gdefja HgG dWa Gddg Hg hYaG Yfg s
(3aj efGbH GdSdWGf bGfUhg GdZhQjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B336s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B439 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJGQjNs